Paul Thompson, with Joanna Bornat, The Voice of the Past, 4th ed. - Van Boeschoten, Riki (Historein, 2018)
Review of Paul Thompson, with Joanna Bornat, The Voice of the Past: Oral History. 4th ed. New York: Oxford University Press, 2017. xii + 484 pp.